Pengaruh Promosi dan Diskon terhadap Kepuasan Pelanggan Toserba Tikung Lamongan - Erly Juliyani Juliyani; M. Ilham Jefri Al Bukori; Anas Alhifni (JOURNAL OF SHARIA ECONOMICS, 2026)
This study aims to analyze the impact of discounts and promotions on customer satisfaction at Toserba Tikung Lamongan. The increasingly competitive retail competition demands businesses to design effective marketing strategies to enhance customer satisfaction as an indicator of business sustainability. This study uses a quantitative approach with a survey method targeting customers who have shopped at Toserba Tikung Lamongan. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the validity, reliability, and relationships between variables. The results of the study show that both discounts and promotions have a positive and significant effect on customer satisfaction. Promotions have a more dominant influence compared to discounts, as reflected in the larger path coefficient and effect size values. The R-square value of 0.857 indicates that 85.7% of the variation in customer satisfaction can be explained by these two variables, meaning the research model has a very strong explanatory power. These findings suggest that a marketing strategy based on effective promotional communication and well-measured discount policies are key determinants in enhancing customer satisfaction in the local retail sector. This research provides practical implications for retail management in designing marketing strategies that focus on creating value and customer experience sustainably.